A New Antagonist of Caenorhabditis elegans Glutamate-Activated Chloride Channels With Anthelmintic Activity - Castro, María Julia; Turani, Ornella; Faraoni, María Belén; Gerbino, Darío; Bouzat, Cecilia (Frontiers in Neuroscience, 2020)
Nematode parasitosis causes significant mortality and morbidity in humans and considerable losses in livestock and domestic animals. The acquisition of resistance to current anthelmintic drugs has prompted the search for new compounds for which the free-living nematode Caenorhabditis elegans has emerged as a valuable platform. We have previously synthetized a small library of oxygenated tricyclic compounds and determined that dibenzo[b,e]oxepin-11(6H)-one (doxepinone) inhibits C. elegans motility. Because doxepinone shows potential anthelmintic activity, we explored its behavioral effects and deciphered its target site and mechanism of action on C. elegans. Doxepinone reduces swimming rate, induces paralysis, and decreases the rate of pharyngeal pumping required for feeding, indicating a marked anthelmintic activity. To identify the main drug targets, we performed an in vivo screening of selected strains carrying mutations in Cys-loop receptors involved in worm locomotion for determining resistance to doxepinone effects. A mutant strain that lacks subunit genes of the invertebrate glutamate-gated chloride channels (GluCl), which are targets of the widely used antiparasitic ivermectin (IVM), is resistant to doxepinone effects. To unravel the molecular mechanism, we measured whole-cell currents from GluClα1/β receptors expressed in mammalian cells. Glutamate elicits macroscopic currents whereas no responses are elicited by doxepinone, indicating that it is not an agonist of GluCls. Preincubation of the cell with doxepinone produces a statistically significant decrease of the decay time constant and net charge of glutamate-elicited currents, indicating that it inhibits GluCls, which contrasts to IVM molecular actions. Thus, we identify doxepinone as an attractive scaffold with promising anthelmintic activity and propose the inhibition of GluCls as a potential anthelmintic mechanism of action.